The role of foreign capital investments and the European Union Funds in management of regional and local development - Ewa Bojar (European Regional Science Association (ERSA), 2004)
A shortfall of capital constitutes a major barrier of regional and local development. Introduced economical and social transformations started a decade ago had opened Polish economy to the inflow of foreign capital. Both the central government as well as regional and even local authorities spent a lot of efforts to attract foreign investments into the country and as a result of these exertions at the end of 2002 foreign investment stock exceeded 65 Bln US dollars, including more than 61 Bln dollars in huge investments (exceeding 1 Mln dollars). The peak inflow of foreign direct investments to Poland was in 2000 when more that 10 Bln US dollars reinforced Polish economy. However, significant drop was observed in the following years (2001 – 7 Bln dollars, 2002 – 6 Bln dollars). Over the course of political and economical transformation of Polish economy and transition into the market-driven economy near 50 thousand business ventures engaging foreign capital were formed. Unfortunately only a little bit more than 700 found favorable environment in the Lublin region. The Lublin region is the third largest region in Poland. As revealed by our survey presently some 22% out of 213 local communities in the region, also called `gminas', recognize the importance of foreign direct investments in stimulating local social and economical development and it is reflected in their development strategies. Joint venture companies with foreign capital operate in 87 gminas of the Lublin region, and 93 local communities successfully applied for structural funds made available by the European Union to the newly accessing countries (PHARE – 32 gminas, SAPARD – 81 gminas). As regards diversification of financial resources to support local development a trail has already been blazed by many local communities successfully attracting foreign capital and the EU funds. The present paper, based on the research carried out by Department of Economics of Lublin University of Technology, surveys the actual role and perspectives of old and emerging opportunities in terms of financing local and regional development.
Keywords: 330